Analysis of 2 novel mutations of PHEX gene inducing X-linked dominant hypophosphatemia rickets in 2 families: Two case reports. Issue 31 (August 2018) - Gao, Yue; Wang, Zhi-Min; Li, Xia-Lian
Abstract: Rationale: X-linked dominant hypophosphatemia rickets (XLH, OMIM 307800) is the most common hereditary hypophosphatemic rickets and characterized by growth retardation, skeletal malformations, dental dysplasia, spontaneous fractures and osteomalacia. PHEX gene was identified for XLH and novel mutations were consistent with loss of function. Patient concerns: Case1: the proband 1 III3 in family 1 was a fourteen-year-old boy with bowing of bilateral legs, obviously enlarged joints, tooth absence and difficulty in walking; X-rays showed bilateral femoral multiple fractures with sclerosis at the fracture edge. Case 2: the proband 2 III2, a five-year-old boy in family 2, showed growth retardation, dental dysplasia, gingiva abscess and bilateral legs malformations; X-rays showed low bone density, delayed bone age, bowing of legs, frayed and widened metaphyses of the distal femurs and proximal tibias. Both of their mothers suffered from skeletal malformations, tooth absence and were performed with osteotomy due to fractures of lower limb. Their biochemical parameters showed hypophosphatemia, elevated alkaline phosphatase. Diagnoses: X-linked dominant hypophosphatemia rickets (XLH). Interventions and outcomes: Treatment with high doses of phosphate and 1, 25-dihydroxyvitamin D3, the height of proband 2 increased 10 cm and femoral Multiple fracture of proband1 almost healed after treatment for 6 months and the patients's PHEX gene was investigated. Lessons: Two novel pathogenic PHEX mutations were found: c.497delG in family 1 and c.388G> T in family 2, both of which caused early termination of translation and produced truncated protein. Serum FGF23 concentration in our XLH patients were obviously higher than the normal and may be related to age to some extent. Early initiation of treatment produces better effect.